Multimedia Development in 1st Grade of Mu'allimin Madrasa of Muhammadiyah Yogyakarta, Indonesia - Muhammad Lailan Arqam (Budapest International Research and Critics University, 2019)
The development of multimedia learning in Kemuhammadiyahan subjects, is one of the efforts made in improving the quality of learning processes and results. With this multimedia learning, it is expected to be able to overcome the problems at hand. This research was conducted at Mu'allimin Madrasa of Muhammadiyah which is located at Letjend Street. S. Parman no. 68 Yogyakart. The result shows that development of multimedia learning in Kemuhammadiyahan subjects is done by developing several aspects, namely: (a) Text Aspect; (b) Color Aspects; (c) Animation and Image Aspects; (d) Material Aspects; (e) Sound Aspects; (f) Interactive aspects.